The usage of data in NHS primary care commissioning: a realist evaluation - Jager, A; Papoutsi, C; Wong, G (BioMed Central, 2023)
Background To improve health outcomes and address mounting costs pressures, policy-makers have encouraged primary care commissioners in the British National Health Service (NHS) to increase the usage of data in decision-making. However, there exists limited research on this topic. In this study, we aimed to understand how and why primary care commissioners use data (i.e. quantitative, statistical information) to inform commissioning, and what outcomes this leads to.